2009
DOI: 10.1159/000220827
|View full text |Cite
|
Sign up to set email alerts
|

Medullary Thyroid Cancer: Molecular Biology and Novel Molecular Therapies

Abstract: Medullary thyroid cancer (MTC) arises from neural-crest-derived parafollicular C cells of the thyroid gland and accounts for approximately 4% of all thyroid cancers. Up to 25–30% of MTC cases occur as inherited disorders while the remaining cases represent the sporadic form of the disease. In this review, the structure and signalling properties of the RET proto-oncogene in its wild-type and mutant forms, and its role in hereditary and sporadic MTC, are discussed. A full data search was performed through PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 291 publications
(193 reference statements)
1
35
0
4
Order By: Relevance
“…showing significant activity in patients with MTC [3]. Noteworthy, we found that one of these agents, sorafenib [38], showed effects on the Ret /Fap-1 system comparable to those described M a n u s c r i p t…”
Section: Multi-target Therapeutics Including Ret Inhibitors Have Recesupporting
confidence: 64%
See 3 more Smart Citations
“…showing significant activity in patients with MTC [3]. Noteworthy, we found that one of these agents, sorafenib [38], showed effects on the Ret /Fap-1 system comparable to those described M a n u s c r i p t…”
Section: Multi-target Therapeutics Including Ret Inhibitors Have Recesupporting
confidence: 64%
“…Tumor regressions in treated animals were observed in association with apoptosis induction and angiogenesis inhibition [15]. Currently, several agents targeting Ret among other kinases are under clinical investigation in thyroid cancers [3,16].…”
Section: Page 4 Of 38mentioning
confidence: 99%
See 2 more Smart Citations
“…В настоящее время идентифицировано множество биомаркеров, и многие из них продемонстрировали весьма обнадеживаю щие результаты в дифференциальной диаг ностике фолликулярных опухолей ЩЖ [4,5,7,9,10]. В то же время работы по идентифи кации циркулирующих биомаркеров начали появляться лишь в течение последних не скольких лет.…”
Section: результаты и их обсуждениеunclassified